2013
DOI: 10.1186/1999-3110-54-18
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-aminolevulinic acid in the salinity stress response of the seeds and seedlings of the medicinal plant Cassia obtusifolia L.

Abstract: BackgroundSoil salinity, one of the major abiotic stresses affecting germination, crop growth, and productivity, is a common adverse environmental factor. The possibility of enhancing the salinity stress tolerance of Cassia obtusifolia L. seeds and seedlings by the exogenous application of 5-aminolevulinic acid (ALA) was investigated.ResultTo improve the salinity tolerance of seeds, ALA was applied in various concentrations (5, 10, 15, and 20 mg/L). To improve the salinity tolerance of seedlings, ALA was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Regardless of the application method used, ALA enhanced gas exchange capacity severally in date palm (P. dactylifera L.) and oilseed rape (B. napus L.) under salinity and cadmium stress (Youssef and Awad 2008;Ali et al 2013b). Moreover, the application of ALA improved chlorophyll fluorescence parameters (including photochemical efficiency of photosystem II (Fv/ Fm), photochemical efficiency (Fv′/Fm′), PSII actual photochemical efficiency (ΦPSII), and photochemical quench coefficient (qP)) in Cassia obtusifolia L. under salt stress were, but the non-photochemical quenching coefficient (NPQ) was decreased, indicating that photochemical activity of PSII can be repaired by ALA (Zhang et al 2013). In addition, under Cd stress, the photosynthetic fluorescence parameters were improved by ALA application (Ali et al 2015).…”
Section: Heightened Photosynthesismentioning
confidence: 98%
“…Regardless of the application method used, ALA enhanced gas exchange capacity severally in date palm (P. dactylifera L.) and oilseed rape (B. napus L.) under salinity and cadmium stress (Youssef and Awad 2008;Ali et al 2013b). Moreover, the application of ALA improved chlorophyll fluorescence parameters (including photochemical efficiency of photosystem II (Fv/ Fm), photochemical efficiency (Fv′/Fm′), PSII actual photochemical efficiency (ΦPSII), and photochemical quench coefficient (qP)) in Cassia obtusifolia L. under salt stress were, but the non-photochemical quenching coefficient (NPQ) was decreased, indicating that photochemical activity of PSII can be repaired by ALA (Zhang et al 2013). In addition, under Cd stress, the photosynthetic fluorescence parameters were improved by ALA application (Ali et al 2015).…”
Section: Heightened Photosynthesismentioning
confidence: 98%
“…First, the ALA concentrations for seed priming employed in the current study (0.002 -0.5 μg mL -1 ) were lower than those in the other investigations. Korkmaz et al (2010) reported that seed soaking with 25 ppm ALA providing chilling stress tolerance of pepper seedling, while Zhang et al (2013) also demonstrated that the exogenous application of ALA at 25 mg L -1 significantly improved SOD, POD and CAT in seedling leaves of Cassia obtusifolia L. under salinity stress. The second possibility is that the scavenging property of the antioxidative enzymes depends on the concentration of ALA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that rice seed primed with 0.2 μg mL -1 ALA had the potential to increase cell division and elongation in the seedlings. ALA stimulated photosynthesis and thus more cellular protein synthesis in the plants (Hotta et al, 1997b;Zhang et al, 2013). Seedlings with a higher relative growth rate will have a denser cellular content, i.e., cell organelles, and thus lower water content of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zhang et al (2013) also reported that chlorophyll content was decreased by NaCl stress in Cassia obtusifolia L, Salinity stress undermines cell membrane permeability and causes the leakage of numerous chlorophylls molecules and reduces chlorophylls content (Mehta et al, 2010). Chlorophylls are essential for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…MDA is the final product of membrane lipid peroxidation; its content and membrane permeability are important indicators to evaluate membrane lipid peroxidation and plasma lemma damage (Salama and Mansour, 2015). Zhang et al (2013) revealed that ALA treatment can increase the anti-lipid peroxidation of the leaves of Cassia obtusifolia L. seedlings exposed to salinity stress by reducing the MDA content in leaves. The NaCl stress treatment induced a significant increase in MDA content in peach seedlings (Table 3).…”
Section: Discussionmentioning
confidence: 99%